Shaping Rights Through European Consensus or Trend - Vincent Martenet (German Law Journal)
The question of when and how a European consensus or trend contributes to shaping rights guaranteed by the European Convention on Human Rights and its Protocols is controversial. The European Court of Human Rights quite often performs an analysis of the laws and practices of the Council of Europe’s Member States or of relevant international material. However, the cases where rights have actually been shaped by a European consensus or trend are quite rare. In the last twenty-five years, some 27 out of 424 judgments on the merits of the Grand Chamber of the Court established a consensus or trend having a “shaping impact” on these rights. Further, only one advisory opinion based on Protocol No. 16 contained comparative law material having such an influence. This Article assesses the intensity of the impact of a consensus or a trend analysis on a judgment’s or an advisory opinion’s ratio decidendi, shows what shaping a right actually means, and suggests that cases that are more prone to a potentially persuasive consensus or trend analysis will typically deal with matters of political or general policy, sensitive moral or ethical issues, or changes in the case law.